Systems Analysis; Solving unconstrained binary quadratic programming problem by global equilibrium search - Shylo, V. P.; Shylo, O. V. (Cybernetics and systems analysis, 2011)
A new algorithm based on global equilibrium search (GES) is developed to solve an unconstrained binary quadratic programming (UBQP) problem. It is compared with the best methods of solving this problem. The GES algorithm is shown to be better both in speed and solution quality.